Hubungan Asosiasi Antara IPK Dengan Waktu Belajar Mahasiswa/i Universitas Sultan Ageng Tirtayasa - Mia Fajriany; Vasthi Khoirun; Widya Arifiani; Sultan Zaki; Nur Aini A (Pusat Riset dan Inovasi Nasional, 2023)
GPA (Grade Point Average) is a reflection of a person's performance while at university which is described in the form of numbers. There are several factors that influence the size of a person's GPA. One factor that may have an influence is the length of study time, because studying in any form is closely related to all lecture activities that support grades. The aim of the research is in response to the desire to understand how certain factors can influence a student's academic achievement and whether there is a relationship between GPA and length of study time. The research method used is the chi-square test of independence as a statistical method and field studies for data collection and processing. The source of research data used by researchers is students from Sultan Ageng Tirtayasa University who were collected through questionnaires. Respondents will be given the choice of a GPA level of more than 3.5 or less than 3.5 and also the length of study time at a level below 2 hours and above 2 hours. Then the answers from the respondents have been collected, then the answers will then be processed and analyzed again to find conclusions. Thus, from the survey, the results of H0 were not rejected and it can be concluded that there is no association between GPA and length of study time.